Optimalisasi Penghimpunan Dana Zakat dalam Mencapai Target di LAZISMU Banyumas - Alwi Rokhman Saifulloh (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Zakat fund collection is one of the main activities of zakat management, every activity in zakat management is aimed at achieving the goal of zakat, namely to improve the people's economy by managing zakat funds that are oriented towards improving the economic conditions of mustahik, so collecting zakat funds must be carried out optimally. To be able to carry out optimal collection, a collection strategy and mechanism is needed. LAZISMU Banyumas implements a strategy and mechanism for collecting zakat funds. The results of collecting zakat at LAZISMU Banyumas are also quite good, and LAZISMU Banyumas has received many national level awards, one of which is the LAZISMU Award in 2021 to become the best financial amil. The purpose of this research is to find out the mechanism for collecting zakat funds at LAZISMU Banyumas and to find out the strategy of LAZISMU Banyumas in achieving the target of collecting zakat funds. This is qualitative field research. Data collection techniques include observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion. Based on the results of this study, it can be concluded that optimizing the collection of zakat funds to achieve targets is carried out by LAZISMU Banyumas, namely by implementing predetermined fundraising strategies such as outreach, direct mail, direct payments to offices, pick up donations, zakat counters, banking channels, QRIS, establishment service offices, online fundraising, and maintenance. The mechanism for collecting zakat funds implemented by LAZISMU Banyumas is by sending socialization notification letters to prospective muzakki, carrying out socialization, and recording the identity of prospective muzakki. LAZISMU Banyumas provides several zakat payment mechanisms. The first is the mechanism for collecting zakat directly at the office, collecting zakat through transfers, and collecting zakat through the pickup and delivery of donations